Eukaryotic elongation factor 2 kinase regulates foam cell formation via translation of CD36. Issue 2 (15th January 2022) - Fernando, Sanuja; Salagaras, Thalia; Schwarz, Nisha; Sandeman, Lauren; Tan, Joanne T. M.; Xie, Jianling; Zareh, Jonar; Jensen, Kirk; Williamson, Anna; Dimasi, Catherine; Chhay, Pich; Toledo‐Flores, Deborah; et al.
Abstract: Eukaryotic elongation factor 2 kinase (eEF2K) is an atypical protein kinase that controls protein synthesis in cells under stress. Although well studied in cancer, less is known about its roles in chronic inflammatory diseases. Here, we examined its regulation of macrophage cholesterol handling in the context of atherosclerosis. eEF2K mRNA expression and protein activity were upregulated in murine bone marrow‐derived macrophages (BMDMs) exposed to oxidized low‐density lipoprotein cholesterol (oxLDL). When incubated with oxLDL, BMDMs from eEF2K knockout ( Eef2k −/− ) mice formed fewer Oil Red O + foam cells than Eef2k +/+ BMDMs (12.5% ± 2.3% vs. 32.3% ± 2.0%, p  < .01). Treatment with a selective eEF2K inhibitor, JAN‐384, also decreased foam cell formation for C57BL/6J BMDMs and human monocyte‐derived macrophages. Disabling eEF2K selectively decreased protein expression of the CD36 cholesterol uptake receptor, mediated by a reduction in the proportion of translationally active Cd36  mRNA. Eef2k −/− mice bred onto the Ldlr −/− background developed aortic sinus atherosclerotic plaques that were 30% smaller than Eef2k +/+ ‐ Ldlr −/− mice after 16 weeks of high cholesterol diet ( p  < .05). Although accompanied by a reduction in plaque CD36 + staining ( p  < .05) and lower CD36 expression in circulating monocytes ( p  < .01), this was not associated with reduced lipid content in plaques as measured by oil red O staining. Finally, EEF2K and CD36  mRNA levels were higher in blood mononuclear cells from patients with coronary artery disease and recent myocardial infarction compared to healthy controls without coronary artery disease. These results reveal a new role for eEF2K in translationally regulating CD36 expression and foam cell formation in macrophages. Further studies are required to explore therapeutic targeting of eEF2K in atherosclerosis.